A Closer Look at Prisons and Prison Inmates - Mowll, Gabriel (Safety and risk in society series., 2020)
"A Closer Look at Prisons and Prison Inmates first explores how inmates perceive prisons in general, as well as particular aspects of the facilities where they serve time. In that sense, and after reviewing the literature regarding prison conditions and inmates' perceptions about prisons, a Prison Perception Scale is developed and assessed. Additionally, the authors examine how popular depictions of women in prison both interrupt and reinforce damaging stereotypes of incarcerated women. A content analysis of the popular Netflix series "Orange is the New Black" is provided in order to examine the hypothesis that incarcerated women are rarely presented as survivors in media. The closing chapter discusses some cause of recidivism if inmates such as lack of socialization, lack of job training, inability to adjust to social pressure, inability to reintegrate into the society after incarceration, lack of social support, mal-adjustment, lack of education, substance abuse, stigmatization and abuse"--